2011
DOI: 10.1007/s00586-011-1696-7
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of the sigmoid colon due to intradiscal spacer dislocation

Abstract: A case of late dislocation of a disc spacer L5/S1 with perforation of the sigmoid colon and transanal passage 4 years after implantation is reported. The objective is to describe an uncommon complication of anterior endoscopic spondylodesis L5/S1. To our knowledge, this is the first report on this rare complication. A 39-year-old patient suffering from a spondylolisthesis L5/S1 (Meyerding grade 2) with bilateral lysis L5 was operated with posterior instrumentation L5/S1 and anterior endoscopic insertion of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In one publication, bowel injury occurred during sacrectomy for tumor removal (34). There were 10 publications in which bowel injury was described after lateral approaches and MIS spinal procedures in the lumbar spine (11,12,(14)(15)(16)21,23,24,27,33). Additionally, one study reported bowel injury after instrumentation failure in a procedure for a spinal deformity (25).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In one publication, bowel injury occurred during sacrectomy for tumor removal (34). There were 10 publications in which bowel injury was described after lateral approaches and MIS spinal procedures in the lumbar spine (11,12,(14)(15)(16)21,23,24,27,33). Additionally, one study reported bowel injury after instrumentation failure in a procedure for a spinal deformity (25).…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, bowel injury occurred during surgery and was noted at the time. Three cases of bowel injury were diagnosed postoperatively due to migration of instrumentation (16,21,27). Abrasion of the intestinal wall in one patient was the result of a migrated screw after a lumbosacral AxiaLIF procedure (33).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bowel injuries are a rare complication of anterior lumbar spinal procedures [6][7][8][9][10][11], but can occur in any lumbar procedure, even posterior approaches [12]. The XLIF procedure is a well-recognized alternative to direct anterior interbody fusion and has many relevant benefits over conventional approaches, with relatively a low rate of complications [1,3,[13][14][15][16][17][18][19], though the risk of bowel injury, while low, does exist.…”
Section: Discussionmentioning
confidence: 99%